Karyotype and Banding Patterns of Chicken Breeds - Musa, H.H.; Li, B.C.; Chen, G.H.; Lanyasunya, T.P.; Xu, Q.; Bao, W.B. (International Journal of Poultry Science, 2005)
Traditional karyotyping is invented in animal research for several decades depend on the analysis of characteristic banding patterns along the length of chromosome. In the present study chicken metaphase chromosomes were obtained by peripheral blood lymphocyte culture techniques, G-band patterns were obtained with trypsin and Giemsa, C-band patterns were treated with barium and the nuclear organizer regions (NORs) were identified by silver staining. All species studied presented a diploid number of 78 chromosomes, with 10 pairs of macro chromosomes including the sex chromosome and 29 pairs of micro chromosomes. G-band patterns were found quite different between breeds. The dark stained of C-band was observed on micro chromosome and W chromosome. Karyotype resemblance near coefficient was possible for breeds clustering. The position of centromers, relative length, arm ratio and the evolutionary distance of chicken breeds was estimated. The application of chromosome karyotype and banding techniques was used to study the origin, evolution and relationship of species, also used for gene location and sex determination. While, in the Medical field was used to identify genetic disease. The techniques was consider as a base for further molecular research, for example FISH.